A novel permeability calculation model to simultaneously quantify the impacts of pore and fracture with full feature size - Li, Minghui; Zhang, Banghong; Wu, Zhouqian; Luo, Shaochen; Lu, Jun; Zhang, Dongming; Xie, Heping (International journal of mining science and technology, 2025)
•A model is proposed to quantify pore-fracture with full feature size impacts on permeability under thermo-mechanical coupling.•Propose a relationship between tortuosity and porosity that accounts for the influence of temperature.•Experimental results validated in the model indicate fractures play a dominant role in the evolution of rock permeability.•The new model superiorly characterizes permeability in fracture-pore structure, compared to traditional or pore-only models. The permeability of rocks is of utmost importance in the exploitation of deep geological resources. Current characterizations of rock permeability typically consider the influence of either pores or fractures alone. However, deep reservoir rock formations are subjected to complex environments with coupling of high temperature and stress. As a result, deep reservoir rocks possess a complex structure comprising of pores and fractures, making it challenging to understand their impact on permeability. Comprehending this relationship is vital for the secure and efficient exploitation of deep geological resources. This study presents a permeability calculation model that enables simultaneously quantify the impacts of pore and fracture with full feature size. The model independently considers large-scale fractures’ fractal properties and tortuosity while also addressing the distribution and size of small-scale pores. A tortuosity expression that incorporates the effects of thermal damage has been developed using the pore geometric elasticity method. Considering the distinct contributions of pores and fractures to rock permeability, a comprehensive rock permeability calculation model is established. This model has two main strengths: it thoroughly characterizes the influence of pore structures on permeability at multiple scales and precisely details how fractal attributes of fractures affect permeability. To validate the applicability of the model, this study conducted seepage experiments and microscopic observations, capturing the variations in permeability under thermo-mechanical coupling, while quantifying the geometric characteristics and spatial distribution of pores and fractures within the rock. By comparing the measured permeability results, the theoretical values demonstrated a commendable fit. In comparison to previous models, this innovative approach more accurately captures various flow characteristics of the rock under the influence of thermo-mechanical coupling.